Queering Crime Reporting: Representing Anti-queer Violence in LGBTQ News Media - Mitchell, Matthew (The British journal of criminology, 2025)
While criminology has studied news media reporting for decades, it has largely overlooked reporting on anti-queer violence and depictions of crime outside mainstream outlets. This article addresses this gap by analysing how anti-queer violence is represented in LGBTQ community media. By analysing 1,295 articles from 11 LGBTQ publications across five Anglophone countries between 2019 and 2021, we examine which forms of anti-queer violence are deemed newsworthy in these outlets. Our analysis reveals that LGBTQ community media emphasize particular types of violence, relationships between victims and perpetrators and contexts of victimization while downplaying or disregarding others. We argue that this selective representation both mirrors and ‘queers’ prevailing norms in mainstream crime news reporting in culturally and criminologically significant ways. In grappling with this tension, we identify and critique several cisheteronormative assumptions embedded in the existing literature on news media representations of crime. Ultimately, our analysis calls for a re-evaluation and revision of the existing discourse within media criminology, urging scholars to engage with a broader range of experiences, communities and narrative practices to understand better how violence is culturally mediated.